Induction chemotherapy and concurrent chemoradiotherapy with cisplatin for T4 nasoethmoidal squamous cell carcinoma: The value of paclitaxel, carboplatin and cetuximab (PCE) - Tanaka, Nobukazu; Enokida, Tomohiro; Okano, Susumu; Fujisawa, Takao; Tanaka, Hideki; Onaga, Ryutaro; Hoshi, Yuta; Kishida, Takuma; Wada, Akihisa; Sato, Masanobu; Takeshita, Naohiro; Fujisawa, Takeshi; et al. (Oral oncology, 2025)
•The optimal therapy for locally advanced sinonasal SCC is still undetermined.•Induction chemotherapy in non-surgically-treated T4 sinonasal SCC was assessed.•IC-PCE yielded an ORR of 80% with a favorable safety profile (Gr3 AEs: 20%).•Adding IC-PCE before chemoradiotherapy provided excellent prognosis (3-y RFS: 90%). Locally advanced nasoethmoidal squamous cell carcinoma (SCC) is rare and often unsuitable for surgical resection. Data on the potential clinical benefits of combining induction chemotherapy (IC) and sequential definitive chemoradiotherapy for this condition is limited. We retrospectively investigated T4 nasoethmoidal SCC patients who underwent proton or photon chemoradiotherapy with curative intent at the National Cancer Center Hospital East between April 2014 and May 2022. Patients were categorized into three groups based on IC regimen: no IC (No-IC), paclitaxel plus carboplatin plus cetuximab (IC-PCE), and docetaxel plus cisplatin plus S-1 (IC-TPS). Twenty-five patients were analyzed (No IC, 9; IC-PCE, 10; and IC-TPS, 6). The IC-PCE group had the highest ratio of Stage IVB to IVA patients. IC-PCE and IC-TPS yielded objective responses in eight (80 %) and two (33 %) patients, respectively. All subjects completed radiotherapy, with the median relative to dose intensity of concurrent cisplatin reaching 100 % in all groups. Complete responses were observed in 22 patients. Three patients in the No IC or IC-TPS group showed a partial response after the completion of planned treatment. On a median follow-up of 42 months, the 3-year recurrence-free survival (RFS) rate was 90.0 % in the IC-PCE group and 33.3 % in the remaining groups. Of note, the IC-PCE group had significantly better RFS (log-rank p-value; 0.023) despite no differences in overall survival, time-to-locoregional progression, or time-to-distant metastasis. Sequential IC-PCE followed by concurrent chemoradiotherapy with cisplatin appears promising as an effective therapeutic strategy for T4 nasoethmoidal SCC.